A qualitative study exploring the experience of the partners of cancer survivors and their views on the role of primary care - Adams, E; Boulton, M; Rose, P; Lund, S; Richardson, A; Wilson, S; Watson, E (2012)
Purpose The partners of cancer survivors may experience distress, anxiety, fear and uncertainty whilst also caring for and supporting a partner who is ill. As they concentrate on the cancer survivor's needs, their own needs may remain unaddressed. Primary care staff may be well placed to support partners as they are generally accessible and may have a better knowledge of the patient's background and family relationships. However, their current involvement in the cancer survivor's and partner's cancer-related care is unclear. This study aimed to describe the experience of the partners of cancer survivors in dealing with cancer-related issues in the first 3 years post-diagnosis, their use of primary care services in relation to these issues and the barriers in doing so and their views on the role that primary care could potentially play in supporting them as carers during this period. Methods Semi-structured interviews with 22 partners of cancer survivors diagnosed within the last 3 years and recruited through six GP practices in the Thames Valley Region of the UK were analysed using the 'framework' approach to thematic analysis. Results Three issues were identified as of particular concern to partners: providing practical support, providing emotional support and managing their own health and well-being. Few partners had sought or received support from primary care specifically for cancer-related issues, indicating confidentiality, lack of knowledge of family relationships and the greater need of the cancer survivor as barriers. Most partners would welcome a proactive approach from primary care and felt that this would provide an opportunity to discuss issues they were concerned about. Conclusions Needs and concerns of the partners of cancer survivors in caring for patients are often not addressed. There is a scope for primary care to elicit these needs and provide greater support. Changes to clinical practice in primary care could lead to greater involvement of and to better outcomes for cancer survivors and their partners. A proactive approach to patients and their partners or other close family members at the time of diagnosis through an offer of support and the inclusion in a designated review appointment at the end of initial treatment would be useful. © Springer-Verlag 2012.